Idea metropolii jako dobra wspólnego w dyskursie prasy lokalnej – perspektywy i postulaty - Neuve-Église, Zuzanna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2025)
The article addresses the issue of creating metropolitan awareness in the Silesian Voivodeship and the role that local press discourse plays in this process. Journalists employ specific linguistic means and strategies to emphasise the significance of the metropolitan area, promote the development of metropolitan management institution, and encourage residents to engage in the idea of the metropolis as a common regional good. The article is based on an analysis of local press discourse from 2007 to 2018. It focuses on the process of shaping collective imagination based on the media image of the metropolis and, in the longer term, the potential formation of lived space and metropolitan citizenship in the context of territorial-administrative changes at the metropolitan level.